Antimicrobial activity and physicochemical properties of Balanites aegyptiaca seed oil - Habieballa, Abdalla Gobara; Alebead, Halima Elfadel; Koko, Madena Komi; Ibrahim, Awad Salim; Wady, Asha Fadllallah (European Journal of Chemistry, 2021)
This study was aimed to assess the antibacterial and antifungal activities of Balanites aegyptiaca seed oil and characterize the physicochemical properties. Seeds were collected from the local central market, Khartoum-Sudan (2019). The samples were dried under shade and grinded, then the oil was extracted with a Soxhlet extractor using n-hexane. The percentage yield of the extract was found to be 25.64%. The seed oil was tested against Pseudomonas aeruginosa (G-), Escherichia coli (G-), Bacillus subtilis (G+), Staphylococcus aureus (G+), and Candida albicans to assess their antimicrobial properties. The extract of B. aegyptiaca seed oil has antimicrobial activity against most of the organisms tested. The fatty acid profile of the B. aegyptiaca seed oil was analyzed by GC/MS. The results revealed that the presence of five fatty acids, including saturated linoleic acid, oleic acid, and unsaturated palmate and stearic acids, also a unique antioxidant compound butylated hydroxytoluene. The physiochemical properties of the seed oil showed that the oil contained kinetic viscosity (57 cp), density (0.917 g/cm3), refractive index (1.472), acid value (49.96 mg/kg), saponification value (248.75 mg/g), ester number (234.79 mg/kg) and peroxide number (0.02 mg/kg). Through physiochemical analysis, it was found that oil can be used for human consumption due to the percentage yield of unsaturated acids (81%). In addition, the results of the antioxidant activity of the seeds oil showed that the seed oil had moderate antioxidant activity.